Whom to Ask for Feedback: Insights for Resource Mobilization From Social Entrepreneurship. Issue 7 (September 2022) - Drencheva, Andreana; Stephan, Ute; Patterson, Malcolm G.
Social entrepreneurs need resources to develop their organizations and catalyze social impact. Existing research focuses on how social entrepreneurs access and use resources, yet it neglects how they search for resource holders. This issue is particularly salient in social entrepreneurs' decisions about whom to approach for interpersonal feedback as a valuable resource. The current literature offers lists of individuals whom social entrepreneurs approach for feedback and implies these individuals can be easily accessed. Thus, it offers little insight into how social entrepreneurs select whom to approach for feedback and why, or why they struggle to access feedback. We conducted an in-depth inductive study based on 82 interviews with 36 nascent social entrepreneurs to investigate how they search for and select individuals to approach for feedback within and outside their social networks through an iterative appraisal process. Our findings start to open the black box of searching for resource holders in the resource mobilization process and offer insights on power and stigma in social entrepreneurship.